2011
DOI: 10.1162/jocn.2010.21536
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of Frequency-following and Frequency-doubling Visual Responses Revealed by Evoked Neural Harmonics

Abstract: Frequency-following and frequency-doubling neurons are ubiquitous in both striate and extrastriate visual areas. However, responses from these two types of neural populations have not been effectively compared in humans because previous EEG studies have not successfully dissociated responses from these populations. We devised a light–dark flicker stimulus that unambiguously distinguished these responses as reflected in the first and second harmonics in the steady-state visual evoked potentials. These harmonics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 54 publications
5
52
0
Order By: Relevance
“…This difference likely relates to findings that harmonics constitute genuine neural responses that code complementary rather than redundant stimulus representations (Pastor et al 2007;Jenkins et al 2011;Kim et al 2011). Further corroborating these findings, we found individual fundamental and harmonic SSR amplitudes to be uncorrelated.…”
Section: Synchrony-related Gain In Pulse-driven Ssrssupporting
confidence: 80%
See 1 more Smart Citation
“…This difference likely relates to findings that harmonics constitute genuine neural responses that code complementary rather than redundant stimulus representations (Pastor et al 2007;Jenkins et al 2011;Kim et al 2011). Further corroborating these findings, we found individual fundamental and harmonic SSR amplitudes to be uncorrelated.…”
Section: Synchrony-related Gain In Pulse-driven Ssrssupporting
confidence: 80%
“…Notably, spectra revealed strong harmonic responses at twice the pulse frequencies (6.28 and 7.24 Hz). We included these pulsedriven harmonics in further analyses because fundamental and harmonic responses have been repeatedly found to reflect different aspects of stimulus processing (Pastor et al 2007;Kim et al 2011;Porcu et al 2013). …”
Section: Electrophysiological Data Analysesmentioning
confidence: 99%
“…To take into account the difference in noise levels between the recordings from each of our observers (Vialatte et al, 2010), we computed the signal-to-noise ratio (SNR) by dividing peak amplitudes by the associated noise, which is defined for a given frequency f by the average amplitude of the two neighbor frequencies (i.e., f Ϫ ␦f and f ϩ ␦f where ␦f gives the frequency resolution of the Fourier analysis, which was 0.5 Hz in our studies). Our analysis focused on the second-harmonic components of the flicker frequencies (i.e., 2f ) because previous studies have found the second-harmonic response to be particularly robust in the SSVEP (Rager and Singer, 1998;Herrmann, 2001;Pei et al, 2002) and highly sensitive for attentional modulation (Pei et al, 2002;Kim et al, 2007Kim et al, ,2011Pastor et al, 2007;Saupe et al, 2009). Indeed, SNRs of the first-harmonic components were either very poor (SNR Ͻ Ͻ 1.5) or did not show any attentional modulations in this experiment.…”
Section: Roi-based Analysis Of the Ssvepmentioning
confidence: 89%
“…Secondly, it may be that the perceptual and cognitive processes underlying VWM encoding operate preferentially on contrast-rectified representations of the stimuli (at least in the context of the stimuli as presented in our task). Indeed, several recent studies have analyzed the second harmonic frequency when using the SSVEP technique concurrent with contrast-reversed stimuli (e.g., black-white pattern reversal (Garcia, Srinivasan, & Serences, 2013; Kim, Grabowecky, Paller, & Suzuki, 2011). Additionally, Kim and colleagues (2011) recently found evidence suggesting that visual-spatial attention modulates the second, but not first, harmonic frequency of the SSVEP signal.…”
Section: Discussionmentioning
confidence: 99%